2022
DOI: 10.5194/acp-22-11795-2022
|View full text |Cite
|
Sign up to set email alerts
|

Ice microphysical processes in the dendritic growth layer: a statistical analysis combining multi-frequency and polarimetric Doppler cloud radar observations

Abstract: Abstract. The dendritic growth layer (DGL), defined as the temperature region between −20 and −10 ∘C, plays an important role for ice depositional growth, aggregation and potentially secondary ice processes. The DGL has been found in the past to exhibit specific observational signatures in polarimetric and vertically pointing radar observations. However, consistent conclusions about their physical interpretation have often not been reached. In this study, we exploit a unique 3-months dataset of mid-latitude wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 94 publications
(154 reference statements)
4
28
1
Order By: Relevance
“…The temperature range in the region where this mode is formed (-15 to -12 • C) is compatible with planar growth of crystals by vapor deposition. It is worth noting that the DL3 signature is, however, different from the ones typically observed in the dendritic growth layer, in which a small updraft, an increase in reflectivity, and a persistent spectral bimodality are often reported (von Terzi et al, 2022), and which is occasionally observed during this case study (see for instance, Fig. 3, around -15 • C between 15:00 and 16:30, or the spectrogram in Fig.…”
Section: Formation Of Large Dropletscontrasting
confidence: 72%
See 2 more Smart Citations
“…The temperature range in the region where this mode is formed (-15 to -12 • C) is compatible with planar growth of crystals by vapor deposition. It is worth noting that the DL3 signature is, however, different from the ones typically observed in the dendritic growth layer, in which a small updraft, an increase in reflectivity, and a persistent spectral bimodality are often reported (von Terzi et al, 2022), and which is occasionally observed during this case study (see for instance, Fig. 3, around -15 • C between 15:00 and 16:30, or the spectrogram in Fig.…”
Section: Formation Of Large Dropletscontrasting
confidence: 72%
“…By examining not only (S)LDR but also the other radar variables, additional insight can be gained. For instance, cloud droplets are often identified by their signature in the form of a narrow, low-reflectivity peak with Doppler velocity close to zero (Li and Moisseev, 2019;Li et al, 2021;von Terzi et al, 2022).…”
Section: Identification Of Hydrometeor Types In Multi-modal Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…This mode was visible in the Doppler spectra obtained by von Terzi et al. (2022). Unfortunately the BASTA radar did not have Doppler spectra capabilities during the Davis campaign, preventing us ascertaining if secondary ice processes were present at these temperatures and thus also whether this might explain the reduced Doppler velocities within the DGL over Davis.…”
Section: Resultsmentioning
confidence: 65%
“…Lower Doppler velocities within the DGL were investigated recently by von Terzi et al. (2022) in the northern mid‐latitudes, who noted that part of the reason is due to updrafts from latent heat released by enhanced depositional growth. However, the main explanation for the reduction of Doppler velocities within the DGL is the generation of high concentrations of small ice crystals associated with secondary ice processes, which acts to reduce the mean velocities.…”
Section: Resultsmentioning
confidence: 88%